Estudo da influência de íons contaminantes na flotação de apatita em coluna - Santos, Mariana Alves dos (2010)
Irreplaceable element for life, phosphorus is the main component of apatite, a mineral present in phosphate rock. The increasing in agriculture productivity would not be possible without the use of fertilizers. However, being a non-renewable resource, the phosphorus is susceptible to depletion. The exploitation of economically mineable deposits of phosphate ore leads to large losses of phosphorus in the stage of processing. In contrast, the demand for fertilizers in the country only increases. Currently, more than half of world production of phosphate concentrate is produced by flotation. The column flotation has been adequate to the processing of complex and low grades ores, that is the case of Brazilian deposits, and also fine size ranges. However, difficulty in concentrating ores of igneous origin may be aggravated in the presence of dissolved ions in process water used in flotation, since the recirculated water increases the ionic concentration. According to the literature, the process of concentration of apatite is strongly affected by the presence of ionic species, since they interact with the surface of apatite particles by changing the efficiency of the flotation process. Thus, the aim of this work was to evaluate the influence of water contaminated with ions F-, Ca2 +, Mg2 + and PO43- provides in the performance of apatite flotation or, in other words, in recovery, P2O5 content and selectivity of the process, to the coarse and fine ores carried out in a flotation column. And through central composite design (CCD), the influence of these ions in the apatite recovery and P2O5 content for low and high concentrations of contaminants. The results showed that the individual effect of each ion studied provided a substantial decrease in recovery, with different sensitivity to the size ranges studied. The most expressive decreases in apatite recovery are related to contaminants calcium and phosphate, where the first had a maximum reduction in the recovery of 58 and 51% for the coarse and fine, respectively, since the calcium consume the collector, reducing the amount available for the apatite collection. Phosphate confirms its strong depressant effect on the apatite particles, since for the coarse particles, there was a reduction in maximum recovery of 55% and 59% for the fines. For the contaminant magnesium, it is clear the critical effect on the process selectivity, related to the gangue minerals Fe2O3 and SiO2, since P2O5 content, in the presence of this ion, suffered a considerable decrease (up to 8 percentage points), independent of particle size. Magnesium, that also react with the collector, was responsible for the sharp increase in the consumption of NaOH, used to adjust the pulp pH, reaching up to 4 times higher compared to the standard test. The influence of fluoride ion represented an increase in the ratio of selectivity P2O5/SiO2, especially for the fine material, indicating a possible depressing effect on the silicate gangue. For the CCD, carried out at low contaminants concentrations, it is clear the interactions between calcium and magnesium with phosphate, contributing to the increase in the recovery, and between magnesium and fluoride, which contributed to the increase in the P2O5 content. This behavior is probably due to the fact that these ions form insoluble compounds among them, removing these ionic species from the system. As for the CCD performed to high contaminants concentrations, all the flotation tests resulted in very low values of recovery and grade. This fact may be associated with the formation of colloidal precipitates in large quantities, leading to indiscriminate coating of the mineral particles present, including apatite, preventing the reagents action.